ADSORPSI Ni(II) DALAM AIR MENGGUNAKAN KOMPOSIT ZEOLIT-MAGNETIT - , ANIS KHOLIFATUR ROSYIDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Composite of zeolite-magnetite has been synthesized from FeSO4.5H2O and FeCl3 by coprecipitation method and applicated as magnetic adsorbent of Ni(II). The aim of this research is to improve the performance zeolite by modification using magnetite. Two gram of activated natural zeolite was added into 100 mL of Fe2+ and Fe3+ solutions with molar ratio of Fe2+ : Fe3+ ( 1:2 ). Then, the addition of 0.1 M NH4OH was forming the composite magnetic- zeolite with pH as high as 11 at 85 Â°C. The composite was sifted and washed by 10-4 M HCl until pH of 7. The effect of contact time was investigated using continue process. This magnetite adsorbent was characterized with X-ray diffraction and fourier transform infrared spectroscopy. The best contact time for synthesizing composite of zeolite magnetite was obtained at 1 minute. The optimum pH of the composite of zeolite magnetite adsorption capacities was 6. The kinetics data correlated well with the pseudo second order Ho equation with the value of rate constant (k) was 1.45 x 10-3 g/mg.min for composite of zeolit magnetite and 1.62 x 10-3 g/mg.min for the activated zeolite. The adsorbent of zeolite-magnetite composi te could be dispersed and removed quickly by external field magnet. Keywords: composite of zeolite-magnetite, coprecipitation, adsorption, kinetics model